Sosialialisasi Strategi Peningkatan UMKM Kreatif Melalui Pemanfaatan CSR Perusahaan - Sudarman, La; Lelawatty, Poniasih; Teheni, Muhammad Tasjiddin; Syarif, Syastriani Isna Putri (LPPM UNINUS, 2023)
CSR is the social responsibility of a corporation which includes legal, economic, ethical and environmental responsibilities. Meanwhile, creative MSME are efforts where business actors carry out various creative ways to increase the competitiveness of their MSME by utilizing CSR funds provided by the company. The CSR obtained by MSME comes from funds provided by PT. Aneka Tambang, Tbk which operates in Pomalaa District, Kolaka Regency. The purpose of this service is to provide information regarding the pattern, application mechanism and form of PT's CSR program. Aneka Tambang, Tbk. The method used in this service is the socialization method which starts with the FGD stage, needs analysis, implementation of activities and evaluation. From the results of the socialization carried out in Pomalaa District, the MSME target partners were very enthusiastic about knowing the pattern, mechanism and form of the company's CSR utilization program to improve the MSME owned by the target partners. The output of this activity is that MSMEs learn about efforts to increase creative MSME through the use of CSR which can be achieved through partnership, community and participatory patterns. The mechanism for obtaining CSR is through the stages of proposal submission, selection, realization and reporting. The forms of the program include developing the capabilities of MSME players, increasing their ability to understand financial management, improving human resources, production and technology and marketing.